Magnetic Sensitivity Distribution of Hall Devices in Antiferromagnetic Switching Experiments - Schreiber, F.; Meer, H.; Schmitt, Christin; Ramos, Rafael; Saitoh, Eiji; Baldrati, L.; Klaeui, M. (Physical Review Applied, 2021)
We analyze the complex impact of the local magnetic spin texture on the transverse Hall-type voltage in device structures utilized to measure magnetoresistance effects. We find a highly localized and asymmetric magnetic sensitivity in the eight-terminal geometries that are frequently used in current-induced switching experiments, for instance, to probe antiferromagnetic materials. Using current-induced switching of antiferromagnetic NiO/Pt as an example, we estimate the change in the spin Hall magnetoresistance signal associated with switching events based on the domain-switching patterns observed via direct imaging. This estimate correlates with the actual electrical data after subtraction of a nonmagnetic contribution. Here, the consistency of the correlation across three measurement geometries with fundamentally different switching patterns strongly indicates a magnetic origin of the measured and analyzed electrical signals.
CRIS-Team Scopus Importer:2023-03-27